EXPERIMENTS AND DESCRIPTIVE ANALYSIS IN THE MARIADB DATABASE CLUSTER SYSTEM TO PREPARE DATA AVAILABILITY - Widiono, Suyud (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2019)
A database server called the Database Management System (DBMS) that relates tables in a database is called the Relational Database Management System (RDBMS). DBMS/RDBMS is a computer program that provides data services for computers or other computer programs. One of the RDBMS type database server (hereinafter referred to as a database server) is MariaDB. The database server is in charge of managing and providing data, so data must always be ready, fast presented, accurate, and safe, it cannot be damaged or even lost. One way to provide this data is to install several database servers using the concept of replication in the Multiple Server Database system. Replication in a cluster server database is a method of installing several database server nodes that allow between node servers to copy each other and distribute data from one node to another database server node, which then synchronizes data between server nodes to maintain data consistency. This study looks for the most optimal number of minimal database server nodes to provide accurate, fast and safe data on the MariaDB Cluster RDBMS. From the results of the replication test from the cluster server database, it can be concluded that the number of 3 (three) node servers can be known to always synchronize and consistency of data between server nodes, so there are 3 (three) nodes of minimum database node with MariaDB RDBMS.